Molecular dynamics investigation on isobaric heat capacity of working fluid in supercritical CO2 Brayton cycle: Effect of trace gas. (January 2022) - Xue, Juan; Nie, Xianhua; Du, Zhenyu; Li, Hong-Rui; Zhao, Li; Zhu, Yu; Wang, Jiajun
Graphical abstract: Highlights: The isobaric heat capacity of CO2 and CO2 /Xe, CO2 /N2 was investigated by MD. The average AAD of isobaric heat capacity of CO2 /N2 was less than 1.3 %. Effects of the addition of Xe and N2 on the isobaric heat capacity were discussed. Abstract: Supercritical CO2 Brayton cycles have become a research hotspot in high-efficiency power production. Adoption of other gas into CO2 is proved to be an effective way to improve the performance of supercritical CO2 cycle. In practice, it is inevitable to mix impurity gas into CO2 . The additive gas would have significant effects on isobaric heat capacity of CO2 system. However, the lack of isobaric heat capacity of CO2 mixture gas over supercritical regions of CO2 poses a challenge in the design and optimization of supercritical CO2 Brayton cycle. In this work, N2 and Xe, whose mole fraction ranges from 1% to 50 %, is considered as an additive gas in CO2 . The isobaric heat capacity of pure CO2, CO2 /Xe and CO2 /N2 binary mixture is calculated via molecular dynamics simulation. Compared to the commonly utilized database REFPROP, it is found that molecular dynamics simulation exhibits comparable and acceptable performance in prediction of the isobaric heat capacity of the mixed CO2 system. The absolute average deviate of isobaric heat capacity of pure CO2 and CO2 /N2 binary mixtures is less than 1% and 1.3 % compared to the REFPROP database, respectively. Then, the effect of the Xe and N2 on the isobaric heat capacity is discussed. The results demonstrated that the isobaric heat capacity would decrease continuously when CO2 is mixed with Xe and N2 . The prediction models and data put forth in this paper offer great values for practical application system involving S-CO2 Brayton cycle.